Psychometric Evaluation of an Islamic Crisis Communication Scale During the COVID-19 Pandemic - Derma Seprianti; Desi Firmasari; Dedy Novriadi; Lety febriana; N. Baskautshar (Socio-Economic and Humanistic Aspects for Township and Industry, 2023)
This study aimed to develop and psychometrically evaluate an instrument to measure three key constructs in religious crisis communication during the COVID-19 pandemic: communication style, message credibility, and public trust in Islamic religious leaders (ulama). Using a quantitative approach, data were collected through a closed-ended questionnaire from a purposive sample of 180 respondents. The instrument was designed to capture three dimensions of communication style (authoritative–directive, empathetic–collaborative, analytical–integrative), three dimensions of message credibility (expertise, trustworthiness, goodwill), and overall public trust. Item validity was examined using item–total correlations, and all items exceeded the minimum r-table threshold, indicating that each item adequately represented its intended construct. Reliability was assessed using Cronbach’s Alpha for each variable, and the coefficients obtained fell within the acceptable range for social science research, demonstrating satisfactory internal consistency. As such, the instrument can be considered both valid and reliable for use in subsequent empirical studies. The primary contribution of this research is methodological: it provides a preliminary, psychometrically tested measurement tool for examining faith-based crisis communication in Muslim contexts. Future research is encouraged to employ this instrument to test structural relationships among communication style, message credibility, public trust, and related behavioral outcomes.